Mitigation of Geometrical Attack in Watermarking Technique Using Support Vector Machine - Agrawal, Ankita; parajapati, Anubha (International Journal of Computer Sciences and Engineering, 2025)
The current decade of watermarking technique faced a problem of geometrical and some other attack. The minimization of security attack in watermarking technique is major issue. For the minimization of geometrical attack used various transformed based technique. The transform based watermarking technique used some well know function such as DWT, DCT and combination of more wavelet based transform function. Now a day used various authors feature selection based watermarking technique. The feature selection based watermarking technique gives better security strength in compression of another transform based technique. In this paper proposed a classification based watermarking technique and reduces the mitigation of geometrical attack for the process of watermark security strength. For the minimization of attack used correlation coefficient matrix for the processing of embedding and the process of embedding done by the pattern generation. The process of pattern generation used support vector machine. The support vector machine is classifier; it classifies the data on the biases of guidance.